Pemetaan Kesiapan Implementasi Akuntansi Sampah pada Pemerintah Indonesia: Sebuah Scoping Review - Firmansyah, Amrie (Jurnal Ilmiah Wahana Akuntansi, 2025)
This study assesses the readiness of the Indonesian public sector to implement municipal waste accounting using a scoping review approach. From an initial set of 24 documents, including national regulations, government accounting frameworks, waste data systems, financing guidelines, institutional studies, and international technical standards, 11 documents met the PRISMA-ScR inclusion criteria for detailed analysis. Findings indicate that although national regulations designate municipal waste management as a mandatory governmental function, they still lack technical guidance for cost measurement and material flow reporting required in waste accounting. The Government Accounting Standards (SAP) also do not include environmental accounting provisions, resulting in aggregated rather than process-based cost records. The National Waste Management Information System (SIPSN) provides physical waste data but does not integrate it with cost information essential for applying waste accounting methods. Institutional limitations remain, including weak inter-agency coordination, inconsistent reporting practices, and the absence of a standardized service cost structure. Meanwhile, international frameworks such as full cost accounting, material flow cost accounting, and World Bank cost guidelines offer compatible methodologies. Overall, significant structural challenges persist, but the potential for development remains substantial